2018
DOI: 10.1111/eip.12720
|View full text |Cite
|
Sign up to set email alerts
|

Is sport an untapped resource for recovery from first episode psychosis? A narrative review and call to action

Abstract: We suggest that sport-based interventions could be an opportunity to provide life skills training, social connectivity and physical activity opportunities in one intervention to individuals recovering from their first psychotic episode. We call for their development, and provide empirically-based recommendations for intervention design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…It is widely acknowledged in the mental health literature that exercise and lifestyle interventions supervised by professionals with relevant training, including physical educators, physiotherapists and exercise physiologists is associated with greater improvements in comparison to unsupervised interventions and/or intervention supervised by other health professionals [31, 32]. Furthermore, previous studies have found that exercise instructors can play an important role in creating a feeling among participants of partaking in a normalised activity, helping to reverse the negative stigma of mental illness [33]. A qualitative review of mental health and physical activity including exercise (in participants with severe and enduring mental health difficulties) also found that exercise instructors played an important role, and were described by participants as key to providing a sense of safety and support [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely acknowledged in the mental health literature that exercise and lifestyle interventions supervised by professionals with relevant training, including physical educators, physiotherapists and exercise physiologists is associated with greater improvements in comparison to unsupervised interventions and/or intervention supervised by other health professionals [31, 32]. Furthermore, previous studies have found that exercise instructors can play an important role in creating a feeling among participants of partaking in a normalised activity, helping to reverse the negative stigma of mental illness [33]. A qualitative review of mental health and physical activity including exercise (in participants with severe and enduring mental health difficulties) also found that exercise instructors played an important role, and were described by participants as key to providing a sense of safety and support [34].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, long-term studies are warranted to explore potential post-intervention adherence, including the potential implications of exercise for participants’ experience of recovery, i.e. how exercising may be used as a means to improve recovery in association with mental health services [33].…”
Section: Discussionmentioning
confidence: 99%
“…Published interventions that combine PA, social connectivity, and life skills development for FEP are scarce. Sport has been forwarded as a useful intervention platform from which to combine these three components (Brooke et al, ). First, sport is a type of PA “involving physical exertion and skill as the primary focus of the activity, with elements of competition where rules and patterns of behaviour governing the activity exist formally through organisations” (Commonwealth of Australia, , p. 7).…”
Section: Introductionmentioning
confidence: 99%
“…Given the documented need for dynamic early‐intervention approaches (Santesteban‐Echarri et al, ), combined with the call for more PA‐based interventions for people with FEP (iPHYS, ) and a recent call to action for further exploration into the use of sport within psychosis recovery (Brooke et al, ), we sought to develop a sport‐based life skills intervention for young people recovering from FEP. As a starting point, an intervention mapping approach was employed (Bartholomew Eldredge et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, sporting activities in normalized contexts can also be an essential element of social inclusion and the fight against stigma and self-stigma [17]. Until now, studies exploring the effects of sports on mental health have focused on the physical and social benefits of playing sports rather than the reduction of stigma or self-stigma [18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%